Six Revision Surgeries for Massive Epidural Fibrosis with Recurrent Pain and Weakness in the Left Lower Extremity - Ho Yong Choi; Dae Jean Jo (Medicina, 2022)
Epidural fibrosis is a common cause of pain after lumbar surgeries. There are no previous reports documenting profound limb weakness associated with epidural fibrosis. A 43-year-old woman uneventfully underwent microscopic discectomy. However, six additional surgeries were needed due to recurrent pain and weakness episodes, several days after the surgery. Operative findings were severe epidural fibrosis around the thecal sac and nerve roots. Epidural fibrosis excision did not prevent recurrent fibrosis; therefore, we performed a lordotic fusion with posterior column shortening to reduce neural tension and nerve-root stretching. Eventually, she became free from recurrent episodes of deteriorations and repetitive surgeries.